Effect of watertable depth and salinity on growth dynamics of Rhodes grass (Chloris gayana) - Chiacchiera, Sebastián; Bertram, Nicolas; Taleisnik, Edith; Jobbagy Gampel, Esteban Gabriel (2017)
Depending on their depth, watertables can have a positive effect on plants by supplying water, a negative effect by creating waterlogged and/or saline conditions or a neutral effect. Rhodes grass (Chloris gayana), a tropical perennial forage adapted to saline soils, floods and droughts, is a viable choice for the lowlands in the Pampas region of Argentina.